Laser powder bed fusion of a Cu-Ni-Al alloy using the compositional grading approach. (1st July 2023) - Wei, Siyuan; Zhao, Yakai; Li, Shi-Hao; Chen, Shilin; Lau, Kwang Boon; Soh, Verner; Lee, Jing Jun; Zhang, Baicheng; Tan, Cheng Cheh; Wang, Pei; Ramamurty, Upadrasta
Abstract: Using a modified laser powder bed fusion (LPBF) technique, a compositionally graded Cu-Ni alloy was fabricated. Through microstructural and mechanical characterization on the samples extracted from it, the addition of 7.6 wt.% Ni to Cu is identified as the minimum required for obtaining a crack-free and nearly-fully-dense coupons using LPBF. Subsequently, 3 wt.% Al was added to the Cu-7.6 wt.% alloy to deplete the solute Ni atoms from the matrix through the precipitation of Ni3 Al upon aging of the LPBF Cu-Ni-Al alloy, which simultaneously enhances the strength and electrical conductance of the alloy. Through this example, we demonstrate the potential of high-throughput screening of alloys suitable for LPBF through the fabrication of the compositionally graded alloys and subsequent alloy design for optimum property combinations. Graphical abstract: Image, graphical abstract